A low-carbon black wear-resistant polypropylene material modified by black mica and a preparation method thereof
Patent Information
- Application Number
- CN202611363552.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-04
- Publication Date
- 2026-10-30
AI Technical Summary
[0005]针对上述问题,本发明的目的在于提供一种黑滑石改性的低炭黑耐磨聚丙烯材料及其制备方法,针对黑滑石在聚丙烯中的界面锚定与片层受控剥离不匹配,连续摩擦过程中容易发生片层滑移、层间剥离和颗粒拔出,进而造成摩擦系数波动、磨耗增加以及磨痕发白或发灰的问题,通过黑滑石表面处理、部分锌中和马来化PP蜡制备、预锚定热混及熔融后侧喂相结合,形成适用于低炭黑聚丙烯材料的界面调控体系
[0028]KH550预水解液雾化处理后,含氨基的连接位点倾向于分布在黑滑石边缘和缺陷处,片层基面不易连续覆盖,使剪切载荷由边缘连接位点传递,同时保留层间滑移路径。部分锌中和马来化PP蜡热混时铺展于氨基富集黑滑石表面,残余酸酐基团可与氨基局部反应,可能形成的羧酸锌离子缔合可限制蜡相迁移,聚丙烯链段则与共聚PP润湿并扩散,由此可形成区别于整体强化界面的局部锚定状态。共聚PP熔融后侧喂预锚定型功能黑滑石,可减少界面连接受剪切破坏及片层过度破碎。摩擦时,局部锚定增加整粒黑滑石脱粘和拔出所需的剪切力,保留的层间路径允许片层有限滑移,使整粒颗粒和团聚磨屑减少,拔出孔穴、犁沟及聚丙烯连带脱落随之减轻。第三体磨粒减少后,摩擦波动和磨耗下降,表面缺陷引起的光散射减弱,使低炭黑材料的磨痕发白或发灰程度降低,黑色外观保持性得到改善。
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] This invention belongs to the field of polypropylene composite material technology, and relates to a black talc-modified low carbon black wear-resistant polypropylene material and its preparation method. Background Technology
[0002] Polypropylene, with its low density, ease of processing, and resistance to chemical media, is commonly used to manufacture black plastic products requiring rigidity, dimensional stability, abrasion resistance, and consistent appearance. Related materials typically use polypropylene as the matrix, adding talc to improve rigidity and dimensional stability, and using carbon black to create the black appearance. Black talc serves both as a filler and an auxiliary colorant; replacing some ordinary talc with black talc can reduce the amount of carbon black used while maintaining the filling effect.
[0003] Black talc is a layered silicate material with low surface energy and few reactive sites on its lamellar base surface. The active sites are relatively concentrated at the edges and defect areas, while the polypropylene matrix is non-polar. The interaction between the two relies primarily on physical wetting and mechanical intercalation. While conventional surface treatments can improve the dispersion of black talc in polypropylene, the treated components tend to concentrate at the lamellar edges and defect areas, making it difficult to form a continuous and consistent interfacial interaction on the lamellar base surface. During melt blending and molding shearing, black talc lamellars also tend to orient along the flow direction, causing the lamellar base surface to become parallel to the material surface. When the material is subjected to continuous friction, the tangential load is transmitted along the lamellar base surface and the low-shear regions between the layers. Insufficient interfacial bonding can lead to interfacial slippage and pull-out of black talc particles, which then enter the friction interface and form third-body abrasive particles. Conversely, excessively strong interfacial bonding can restrict controlled peeling of the lamellars along the interlayer direction, making it difficult to continuously form a stable lamellar transfer layer at the friction interface.
[0004] Therefore, existing black talc-filled polypropylene has a mismatch between interface anchoring and controlled peeling of flakes under low carbon black conditions. During continuous friction, flake slippage, interlayer peeling and particle pull-out are prone to occur, which in turn causes fluctuations in the coefficient of friction, increased wear, and whitening or graying of the wear marks, affecting the stable maintenance of the black appearance. Summary of the Invention
[0005] To address the aforementioned problems, the present invention aims to provide a low-carbon-black wear-resistant polypropylene material modified with black talc and its preparation method. Addressing the mismatch between the interfacial anchoring of black talc in polypropylene and the controlled peeling of the flakes, which easily leads to flake slippage, interlayer peeling, and particle pull-out during continuous friction, resulting in fluctuations in the coefficient of friction, increased wear, and whitening or graying of the wear marks, the present invention combines black talc surface treatment, partial zinc neutralization of maleic PP wax preparation, pre-anchoring hot mixing, and post-melting side feeding to form an interfacial control system suitable for low-carbon-black polypropylene materials.
[0006] To achieve this objective, the present invention adopts the following technical solution:
[0007] In a first aspect, the present invention provides a method for preparing a talc-modified low-carbon-black abrasion-resistant polypropylene material, the preparation method comprising:
[0008] S1: The pre-hydrolyzed solution of 3-aminopropyltriethoxysilane (KH550) is atomized and sprayed into continuously agitated black talc powder, and then subjected to heating and aging treatments to obtain amino-enriched black talc.
[0009] S2: Zinc oxide (ZnO) is mixed with polypropylene wax (PP wax) to obtain wax-supported ZnO predispersant; maleic anhydride-grafted polypropylene wax (maleic anhydride-grafted PP wax) and fatty alcohol are added to a co-rotating twin-screw extruder for reaction, and then the wax-supported ZnO predispersant is added to continue the reaction to obtain partially zinc-neutralized maleic PP wax.
[0010] S3: The amino-enriched black talc is hot-mixed with the partially zinc-neutralized maleic PP wax to obtain pre-anchored functional black talc.
[0011] S4: Copolymer polypropylene (copolymer PP) and PP carrier carbon black masterbatch are added to a co-rotating twin-screw extruder. After the copolymer PP melts, the pre-anchored functional black talc is added through the side feed port. After melt blending, a black talc-modified low carbon black wear-resistant polypropylene material is obtained.
[0012] Preferably, the D50 of the black talc powder is 3-7 μm. The black talc powder is dried at 100-120℃ for 2-4 hours to obtain dried black talc.
[0013] Preferably, KH550 is added to a mixed solvent to prepare a silane solution with a KH550 mass concentration of 5-10 wt.%. The mixed solvent consists of ethanol and water, wherein the volume fraction of ethanol is 80-90 vol.%, and the remainder is water. The pH of the silane solution is adjusted to 4.5-5.5 with acetic acid, and the solution is allowed to stand at 15-25°C for 30-60 minutes for hydrolysis to obtain a KH550 pre-hydrolyzed solution.
[0014] Preferably, the dried black talc is added to a high-speed mixer and continuously agitated at 60-70℃ and 600-1200rpm, then atomized and sprayed into the KH550 pre-hydrolyzed solution. The mass ratio of the black talc powder to KH550 is 100:(0.4-0.6), and the spraying time is 10-30min. After spraying, the temperature is raised to 80-95℃ and mixing is continued for 10-30min, followed by maturation at 105-115℃ for 20-40min. After cooling, it is sieved to obtain amino-enriched black talc.
[0015] Preferably, the primary particle size of the ZnO is 20-100 nm, and the softening point of the PP wax is 100-130℃. The mass ratio of ZnO to PP wax is (18-22):(82-78). ZnO and PP wax are added to a closed hot mixer and mixed at 300-800 rpm for 10-30 minutes at a temperature 10-20℃ higher than the softening point of the PP wax and not exceeding 150℃. The mixture is then cooled and crushed to obtain a wax-loaded ZnO pre-dispersion.
[0016] Preferably, the maleic anhydride-grafted PP wax has a maleic anhydride grafting amount of 2.5-4.0 wt.% and a softening point of 100-125℃. The fatty alcohol is hexadecyl alcohol or octadecyl alcohol, and the molar ratio of the grafted anhydride group to the fatty alcohol in the maleic anhydride-grafted PP wax is 1:(0.40-0.55). The maleic anhydride-grafted PP wax and fatty alcohol are added to a co-rotating twin-screw extruder through the main feed port and reacted at 145-165℃ for 1-3 minutes.
[0017] Preferably, the mass ratio of the maleic anhydride-grafted PP wax to the wax-supported ZnO predispersant is 100:(1.0-1.4). After adding the wax-supported ZnO predispersant, the reaction is carried out at 150-165℃ for 1.5-3 minutes. During the reaction, the screw speed is 150-350 rpm, the total residence time of the material is 3-5 minutes, and the latter part is vacuum degassing under an absolute pressure of 10-40 kPa. After extrusion granulation, a partially zinc-neutralized maleic PP wax is obtained.
[0018] Preferably, the amino-enriched black talc is heated to 125-155°C, and then the partially zinc-neutralized maleic PP wax is added. The mass ratio of the amino-enriched black talc to the partially zinc-neutralized maleic PP wax is 100:(7-9), and the mixture is hot-mixed at 300-800 rpm for 8-20 minutes. After hot mixing, the mixture is cooled, crushed, and sieved to obtain pre-anchored functional black talc.
[0019] Preferably, the carbon black content in the PP carrier carbon black masterbatch is 35-45 wt.%. Based on a total mass of 100 wt.% of the low-carbon-black abrasion-resistant polypropylene material modified with black talc, the amount of pre-anchored functional black talc added is 15-24 wt.%, the amount of carbon black added is 0.25-0.50 wt.%, the amounts of antioxidant 1010 and antioxidant 168 added are 0.10-0.30 wt.%, and the balance is copolymerized PP. The amount of PP carrier carbon black masterbatch added is calculated based on the actual carbon black content therein.
[0020] Preferably, the melt blending temperature is 180-210℃, the screw speed is 200-400rpm, and the melt blending time is 1-3min. The pre-anchored functional black talc is added through the side feed port and then subjected to medium shear mixing and distribution mixing sequentially. The subsequent stage involves vacuum degassing under an absolute pressure of 10-40kPa, followed by extrusion granulation to obtain a black talc-modified low-carbon-black wear-resistant polypropylene material.
[0021] This invention also provides a low-carbon-black, wear-resistant polypropylene material modified with black talc obtained by the above preparation method. The material comprises copolymer PP, carbon black, and pre-anchored functional black talc. The pre-anchored functional black talc comprises amino-enriched black talc and partially zinc-neutralized maleic PP wax. The amino-enriched black talc comprises black talc powder and a hydrolysis condensate of KH550. The partially zinc-neutralized maleic PP wax is formed by a melt reaction of maleic anhydride-grafted PP wax, fatty alcohol, ZnO, and PP wax.
[0022] KH550 undergoes hydrolysis in a mixed solvent of ethanol and water, forming hydrolysates containing silanol groups. During atomization spraying and subsequent curing, the silanol groups can condense with the hydroxyl groups on the surface of black talc, or they may be deposited on the particle surface through silanol self-condensation. Because the edges and defect areas of black talc lamellars have relatively more exposed hydroxyl groups, KH550 tends to accumulate in these areas, retaining amino sites on the particle surface; the lamellar basal surface has fewer reactive sites, thus making it difficult to form a continuous covalent coating.
[0023] After ZnO is pre-dispersed in PP wax, the wax phase separates the particles, reducing the likelihood of agglomeration when ZnO directly enters the maleic anhydride-grafted PP wax. When the maleic anhydride-grafted PP wax reacts with fatty alcohols, the hydroxyl groups of the fatty alcohols can attack the anhydride groups and cause anhydride ring cleavage, forming a half-ester structure containing ester and carboxyl groups. Subsequently, the wax-supported ZnO pre-dispersed material is added; some carboxyl groups can react with ZnO in an acid-base reaction, potentially forming a zinc carboxylate structure. Due to the solid-liquid interface and reaction pathway limitations, unneutralized carboxyl groups, residual anhydride groups, and a small amount of unreacted ZnO may still remain in the system. Local ionic association can occur between the potentially formed zinc carboxylate regions, limiting the relative migration of adjacent wax segments, but without constituting continuous chemical cross-linking.
[0024] When amino-enriched black talc is thermally mixed with partially zinc-neutralized maleic PP wax, the softened wax phase spreads onto the surface of the black talc. The primary amino groups retained in the KH550 hydrolysis condensate can undergo ring-opening reactions with accessible residual anhydride groups, potentially forming interfacial connections where amide and carboxyl groups coexist. Unreacted amino groups can also form hydrogen bonds, acid-base associations, or coordinate adsorption with carboxyl or zinc carboxylic acid regions. These interactions mainly occur at local contact sites, restricting the migration of partially zinc-neutralized maleic PP wax on the black talc surface while preventing continuous coating of the entire basal surface of the black talc, thus forming a pre-anchored functional black talc.
[0025] Pre-anchored talc is added through the side feed port after the copolymerized PP has melted, which shortens the melting, conveying, and shearing process, reducing excessive fragmentation of the talc sheets and separation of the interfacial wax phase. The polypropylene segments in the maleic anhydride-grafted PP wax and the PP wax can be wetted by the copolymerized PP melt and interdiffusion occurs between them. Limited segmental entanglement may occur between longer segments, establishing a load transfer path between the localized bonding sites on the talc surface and the continuous polypropylene phase. Extrusion shearing still promotes the orientation of the talc sheets along the flow direction, but the pre-formed surface bonding reduces the possibility of direct separation between particles and the interfacial wax phase during the orientation process.
[0026] When frictional tangential stress acts on black talc flakes, local interface bonding can increase the shear force required for the debonding and pull-out of whole particles, while limited slippage can still occur on the non-continuously covered flake base surface and interlayer region. Thin flake-like wear debris formed by localized peeling may spread along the friction direction, correspondingly reducing the number of whole black talc or agglomerated particles entering the friction interface. This reduces cavitation, plowing, and the shedding of surrounding polypropylene caused by particle pull-out, and also lowers the resistance variation caused by the periodic entry of third-body particles into the friction zone. With reduced surface micropores, pits, and raised edges, light scattering in the wear track area weakens, reducing the whitening or graying of the wear track and the degree of friction coefficient fluctuation during continuous friction.
[0027] Compared with the prior art, the beneficial effects of the present invention are as follows:
[0028] After atomization treatment with KH550 pre-hydrolyzed solution, amino-containing linkage sites tend to be distributed at the edges and defects of the black talc, making it difficult for the lamellar substrate to be continuously covered. This allows shear loads to be transferred through the edge linkage sites while preserving interlayer slip paths. Partial zinc neutralization of maleic PP wax spreads on the surface of amino-enriched black talc during hot mixing. Residual anhydride groups can react locally with the amino groups, and the possible association of zinc carboxylic acid ions can limit wax phase migration. Polypropylene segments wet and diffuse with the copolymerized PP, thus forming a localized anchoring state distinct from the overall reinforced interface. Side-feeding pre-anchored functional black talc after copolymerized PP melting reduces shear damage to interfacial connections and excessive lamellar fragmentation. During friction, localized anchoring increases the shear force required for the unbinding and pull-out of whole black talc particles. The preserved interlayer paths allow for limited lamellar slip, reducing whole particles and agglomerated wear debris, and consequently mitigating pull-out pits, furrows, and polypropylene detachment. With the reduction of third-body abrasive particles, friction fluctuations and wear decrease, and light scattering caused by surface defects is weakened, which reduces the whitening or graying of wear marks on low-carbon black materials and improves the retention of black appearance. Detailed Implementation
[0029] The technical solution of the present invention will be described in detail below with reference to specific embodiments. The embodiments described herein are specific implementations of the present invention and are used to illustrate the concept of the present invention; these descriptions are explanatory and exemplary and should not be construed as limiting the implementation of the present invention or the scope of protection of the present invention. In addition to the embodiments described herein, those skilled in the art can also adopt other obvious technical solutions based on the content disclosed in the claims and the specification of this application. These technical solutions include technical solutions that employ any obvious substitutions and modifications made to the embodiments described herein.
[0030] The chemical reagents used in the embodiments and comparative examples of this invention are all commercially available products and have not undergone further purification or processing.
[0031] Example 1
[0032] This embodiment provides a talc-modified low-carbon-black abrasion-resistant polypropylene material and its preparation method. The preparation method specifically includes the following steps:
[0033] S1: Black talc powder with a D50 of 3 μm was dried at 120℃ for 3 h to obtain dried black talc; KH550 was added to a mixed solvent to prepare a silane solution with a KH550 mass concentration of 8 wt.%, wherein the volume ratio of ethanol to water was 80:20, the pH was adjusted to 5.5 with acetic acid, and the solution was allowed to stand at 20℃ for 60 min to hydrolyze, to obtain a KH550 pre-hydrolyzed solution; the dried black talc was added to a high-speed mixer and continuously stirred at 60℃ and 900 rpm, and the KH550 pre-hydrolyzed solution was atomized and sprayed, wherein the mass ratio of black talc to KH550 was 100:0.5, and sprayed for 30 min; after spraying, the temperature was raised to 88℃ and mixed for 10 min, and then cured at 115℃ for 30 min. After cooling, the solution was sieved to obtain amino-enriched black talc.
[0034] S2: ZnO with a primary particle size of 50nm and PP wax were added to a closed hot mixer at a mass ratio of 22:78. The mixing temperature was controlled to be 15℃ higher than the measured softening point of PP wax but not higher than 150℃. The mixture was mixed at 300rpm for 20min, cooled, and crushed to obtain wax-loaded ZnO pre-dispersion. Octadecyl alcohol was selected as the fatty alcohol. Maleic anhydride-grafted PP wax and octadecyl alcohol were added to a co-rotating twin-screw extruder through the main feed port at a molar ratio of grafted anhydride groups to octadecyl alcohol of 1:0.40. The mixture was reacted at 155℃ for 2min. Wax-loaded ZnO pre-dispersion was added, with a mass ratio of maleic anhydride-grafted PP wax to wax-loaded ZnO pre-dispersion of 100:1.2. The mixture was reacted at 150℃ for 2min. The screw speed was 350rpm, the total material residence time was 4.5min, and the subsequent stage was vacuum degassing under an absolute pressure of 25kPa. The mixture was then extruded and granulated to obtain partially zinc-neutralized maleic PP wax.
[0035] S3: Add amino-enriched black talc to a hot mixer and heat it to 140°C. Then add some zinc to neutralize the maleic PP wax. The mass ratio of amino-enriched black talc to the zinc-neutralized maleic PP wax is 100:7. Heat mix at 600 rpm for 20 minutes, cool, crush and sieve to obtain pre-anchored functional black talc.
[0036] S4: PP carrier carbon black masterbatch with a carbon black content of 40 wt.% was selected. Based on a total feed mass of 100 wt.%, 24 wt.% pre-anchored functional black talc, 0.625 wt.% PP carrier carbon black masterbatch, 0.20 wt.% antioxidant 1010, 0.30 wt.% antioxidant 168, and 74.875 wt.% copolymer PP were added, with a carbon black content of 0.25 wt.%. The copolymer PP, PP carrier carbon black masterbatch, antioxidant 1010, and antioxidant 168 were fed into a co-rotating twin-screw extruder through the main feed port. After the copolymer PP melted, the pre-anchored functional black talc was added through the side feed port. The mixture was melt-blended at 195℃ and 400 rpm for 2 minutes. After the side feed port, medium shear mixing and distribution mixing were performed sequentially. The final stage was vacuum-degassed under an absolute pressure of 10 kPa, followed by extrusion granulation to obtain a black talc-modified low-carbon-black wear-resistant polypropylene material.
[0037] Example 2
[0038] This embodiment provides a talc-modified low-carbon-black abrasion-resistant polypropylene material and its preparation method. The preparation method specifically includes the following steps:
[0039] S1: Black talc powder with a D50 of 7 μm was dried at 110℃ for 2 h to obtain dried black talc; KH550 was added to a mixed solvent to prepare a silane solution with a KH550 mass concentration of 10 wt.%, wherein the volume ratio of ethanol to water was 85:15, the pH was adjusted to 4.5 with acetic acid, and the solution was allowed to stand at 15℃ for 45 min to hydrolyze, to obtain a KH550 pre-hydrolyzed solution; the dried black talc was added to a high-speed mixer and continuously stirred at 68℃ and 1200 rpm, and the KH550 pre-hydrolyzed solution was atomized and sprayed, wherein the mass ratio of black talc to KH550 was 100:0.4, and sprayed for 20 min; after spraying, the temperature was raised to 80℃ and mixed for 25 min, and then matured at 108℃ for 40 min. After cooling, the solution was sieved to obtain amino-enriched black talc.
[0040] S2: ZnO with a primary particle size of 20nm and PP wax were added to a closed hot mixer at a mass ratio of 20:80. The mixing temperature was controlled to be 10℃ higher than the measured softening point of PP wax but not higher than 150℃. The mixture was mixed at 600rpm for 30min, cooled, and crushed to obtain wax-loaded ZnO pre-dispersion. Cetyl alcohol was selected as the fatty alcohol. Maleic anhydride-grafted PP wax and cetyl alcohol were added to a co-rotating twin-screw extruder through the main feed port at a molar ratio of grafted anhydride groups to cetyl alcohol of 1:0.50. The mixture was reacted at 145℃ for 1min. Wax-loaded ZnO pre-dispersion was added, with a mass ratio of maleic anhydride-grafted PP wax to wax-loaded ZnO pre-dispersion of 100:1.4. The mixture was reacted at 160℃ for 1.5min. The screw speed was 250rpm, the total residence time of the material was 3min, and the subsequent stage was vacuum degassing under an absolute pressure of 40kPa. The mixture was then extruded and granulated to obtain partially zinc-neutralized maleic PP wax.
[0041] S3: Add amino-enriched black talc to a hot mixer and heat it to 155°C. Then add some zinc to neutralize the maleic PP wax. The mass ratio of amino-enriched black talc to the zinc-neutralized maleic PP wax is 100:8. Heat mix at 300 rpm for 12 minutes, cool, crush and sieve to obtain pre-anchored functional black talc.
[0042] S4: PP carrier carbon black masterbatch with a carbon black content of 35 wt.% was selected. Based on a total feed mass of 100 wt.%, 18 wt.% pre-anchored functional black talc, 1.143 wt.% PP carrier carbon black masterbatch, 0.30 wt.% antioxidant 1010, 0.15 wt.% antioxidant 168, and 80.407 wt.% copolymer PP were added, with a carbon black content of 0.40 wt.%. The copolymer PP, PP carrier carbon black masterbatch, antioxidant 1010, and antioxidant 168 were fed into a co-rotating twin-screw extruder through the main feed port. After the copolymer PP melted, the pre-anchored functional black talc was added through the side feed port. The mixture was melt-blended at 210℃ and 300 rpm for 1 min. After the side feed port, medium shear mixing and distribution mixing were performed sequentially. The final stage was vacuum-degassed under an absolute pressure of 25 kPa, followed by extrusion granulation to obtain a black talc-modified low-carbon-black wear-resistant polypropylene material.
[0043] Example 3
[0044] This embodiment provides a talc-modified low-carbon-black abrasion-resistant polypropylene material and its preparation method. The preparation method specifically includes the following steps:
[0045] S1: Black talc powder with a D50 of 5 μm was dried at 100℃ for 3.5 h to obtain dried black talc; KH550 was added to a mixed solvent to prepare a silane solution with a KH550 mass concentration of 7 wt.%, wherein the volume ratio of ethanol to water was 90:10, the pH was adjusted to 5.2 with acetic acid, and the solution was allowed to stand at 22℃ for 30 min to hydrolyze, to obtain a KH550 pre-hydrolyzed solution; the dried black talc was added to a high-speed mixer and continuously stirred at 65℃ and 600 rpm, and the KH550 pre-hydrolyzed solution was atomized and sprayed, wherein the mass ratio of black talc to KH550 was 100:0.6, and sprayed for 25 min; after spraying, the temperature was raised to 95℃ and mixed for 20 min, and then cured at 105℃ for 25 min. After cooling, the solution was sieved to obtain amino-enriched black talc.
[0046] S2: ZnO with a primary particle size of 100nm and PP wax are added to a closed hot mixer at a mass ratio of 18:82. The mixing temperature is controlled to be 18℃ higher than the measured softening point of PP wax but not higher than 150℃. The mixture is mixed at 800rpm for 15min, cooled and crushed to obtain wax-loaded ZnO pre-dispersion. Octadecyl alcohol is selected as the fatty alcohol. Maleic anhydride-grafted PP wax and octadecyl alcohol are added to a co-rotating twin-screw extruder through the main feed port at a molar ratio of grafted anhydride groups to octadecyl alcohol of 1:0.55. The mixture is reacted at 160℃ for 3min. Wax-loaded ZnO pre-dispersion is added, with a mass ratio of maleic anhydride-grafted PP wax to wax-loaded ZnO pre-dispersion of 100:1.1. The mixture is reacted at 165℃ for 1.5min. The screw speed is 150rpm, the total material residence time is 5min, and the subsequent stage is vacuum degassing under an absolute pressure of 20kPa. The mixture is then extruded and granulated to obtain partially zinc-neutralized maleic PP wax.
[0047] S3: Add amino-enriched black talc to a hot mixer and heat it to 125°C. Then add some zinc to neutralize the maleic PP wax. The mass ratio of amino-enriched black talc to the zinc-neutralized maleic PP wax is 100:8.5. Heat mix at 800 rpm for 8 minutes, cool, crush and sieve to obtain pre-anchored functional black talc.
[0048] S4: PP carrier carbon black masterbatch with a carbon black content of 45 wt.% was selected. Based on a total feed mass of 100 wt.%, 15 wt.% pre-anchored functional black talc, 1.111 wt.% PP carrier carbon black masterbatch, 0.10 wt.% antioxidant 1010, 0.20 wt.% antioxidant 168, and 83.589 wt.% copolymer PP were added, with a carbon black content of 0.50 wt.%. The copolymer PP, PP carrier carbon black masterbatch, antioxidant 1010, and antioxidant 168 were fed into a co-rotating twin-screw extruder through the main feed port. After the copolymer PP melted, the pre-anchored functional black talc was added through the side feed port. The mixture was melt-blended at 180℃ and 250 rpm for 3 minutes. After the side feed port, medium shear mixing and distribution mixing were performed sequentially. The final stage was vacuum-degassed under an absolute pressure of 40 kPa, followed by extrusion granulation to obtain a black talc-modified low-carbon-black wear-resistant polypropylene material.
[0049] Example 4
[0050] This embodiment provides a talc-modified low-carbon-black abrasion-resistant polypropylene material and its preparation method. The preparation method specifically includes the following steps:
[0051] S1: Black talc powder with a D50 of 6 μm was dried at 115 °C for 4 h to obtain dried black talc; KH550 was added to a mixed solvent to prepare a silane solution with a KH550 mass concentration of 5 wt.%, wherein the volume ratio of ethanol to water was 88:12, the pH was adjusted to 5.0 with acetic acid, and the solution was allowed to stand at 25 °C for 50 min to hydrolyze, to obtain a KH550 pre-hydrolyzed solution; the dried black talc was added to a high-speed mixer and continuously stirred at 70 °C and 1000 rpm, and the KH550 pre-hydrolyzed solution was atomized and sprayed, wherein the mass ratio of black talc to KH550 was 100:0.55, and sprayed for 10 min; after spraying, the temperature was raised to 90 °C and mixed for 30 min, and then matured at 112 °C for 20 min. After cooling, the solution was sieved to obtain amino-enriched black talc.
[0052] S2: ZnO with a primary particle size of 70nm and PP wax were added to a closed hot mixer at a mass ratio of 21:79. The mixing temperature was controlled to be 20℃ higher than the measured softening point of PP wax but not higher than 150℃. The mixture was mixed at 500rpm for 10min, cooled, and crushed to obtain wax-loaded ZnO pre-dispersion. Cetyl alcohol was selected as the fatty alcohol. Maleic anhydride-grafted PP wax and cetyl alcohol were added to a co-rotating twin-screw extruder through the main feed port at a molar ratio of grafted anhydride groups to cetyl alcohol of 1:0.45. The mixture was reacted at 165℃ for 1.5min. Wax-loaded ZnO pre-dispersion was added, with a mass ratio of maleic anhydride-grafted PP wax to wax-loaded ZnO pre-dispersion of 100:1.0. The mixture was reacted at 158℃ for 3min. The screw speed was 300rpm, the total material residence time was 5min, and the subsequent stage was vacuum degassing under an absolute pressure of 10kPa. The mixture was then extruded and granulated to obtain partially zinc-neutralized maleic PP wax.
[0053] S3: Add amino-enriched black talc to a hot mixer and heat it to 145°C. Then add some zinc to neutralize the maleic PP wax. The mass ratio of amino-enriched black talc to the zinc-neutralized maleic PP wax is 100:9. Heat mix at 500 rpm for 16 minutes, cool, crush and sieve to obtain pre-anchored functional black talc.
[0054] S4: PP carrier carbon black masterbatch with a carbon black content of 42wt.% is selected. Based on a total feed weight of 100 wt.%, 20 wt.% of pre-anchored functional black talc, 0.833 wt.% of PP carrier carbon black masterbatch, 0.25 wt.% of antioxidant 1010, 0.10 wt.% of antioxidant 168, and 78.817 wt.% of copolymer PP were added, with a carbon black content of 0.35 wt.%. The copolymer PP, PP carrier carbon black masterbatch, antioxidant 1010, and antioxidant 168 were fed into a co-rotating twin-screw extruder through the main feed port. After the copolymer PP melted, the pre-anchored functional black talc was added through the side feed port. The mixture was melt-blended at 200℃ and 200 rpm for 2.5 min. After the side feed port, medium shear mixing and distribution mixing were performed sequentially. The final stage was vacuum degassing under an absolute pressure of 20 kPa, followed by extrusion granulation to obtain a black talc-modified low carbon black wear-resistant polypropylene material.
[0055] Comparative Example 1
[0056] This comparative example provides a black talc-modified low-carbon black wear-resistant polypropylene material and its preparation method. The difference from Example 1 is that an ethanol-water blank solution without KH550 is used, and the black talc is treated under the same spraying, heating and curing conditions as in Example 1. Other operating steps and process parameters are exactly the same as in Example 1.
[0057] Comparative Example 2
[0058] This comparative example provides a black talc-modified low-carbon-black wear-resistant polypropylene material and its preparation method. The difference from Example 1 is that ZnO is not added in step S2, and the wax-loaded ZnO pre-dispersed material is replaced with an equal mass of PP wax to obtain zinc-free maleated PP wax. Other operation steps and process parameters are exactly the same as in Example 1.
[0059] Comparative Example 3
[0060] This comparative example provides a low-carbon-black wear-resistant polypropylene material modified with black talc and its preparation method. The difference from Example 1 is that step S3 is omitted. In step S4, after the copolymerized PP is melted, 22.43 wt.% of amino-enriched black talc and 1.57 wt.% of partially neutralized maleic PP wax are added through the side feed port. Other operating steps and process parameters are exactly the same as in Example 1.
[0061] Comparative Example 4
[0062] This comparative example provides a black talc-modified low-carbon-black wear-resistant polypropylene material and its preparation method. The difference from Example 1 is that in step S4, the pre-anchored functional black talc is added to the co-rotating twin-screw extruder together with the copolymer PP, PP carrier carbon black masterbatch, antioxidant 1010 and antioxidant 168 through the main feed port, instead of being added through the side feed port after the copolymer PP has melted. Other operating steps and process parameters are exactly the same as in Example 1.
[0063] The performance of the black talc-modified low-carbon-black abrasion-resistant polypropylene materials of Examples 1-4 and Comparative Examples 1-4 was tested, and the specific process is as follows:
[0064] The materials obtained from each embodiment and comparative example were injection molded into 30mm×7mm×6mm samples under the same conditions. The barrel temperature of the injection molding machine was 190℃, 200℃, 210℃ and 210℃ respectively, the nozzle temperature was 210℃, the mold temperature was 40℃, the injection speed was 50mm / s, the injection pressure was 80MPa, the holding pressure was 50MPa, the holding time was 15s, and the cooling time was 30s. The length direction of the sample was consistent with the melt flow direction, and the same side was used as the friction surface. After conditioning under standard environmental conditions (23±2℃, 50±10%RH) for 48h, the samples were tested. Five parallel samples were set up in each group.
[0065] Sliding friction and wear performance test: According to GB / T 3960-2016, a quenched No. 45 steel friction ring with an outer diameter of 40 mm and a width of 10 mm was used. The test was conducted continuously for 2 hours under a load of 196 N, a rotational speed of 200 rpm, and dry friction conditions. Loose wear debris was removed from the sample surface before and after the test. The sample mass was weighed using an analytical balance with an accuracy of 0.1 mg. The density of each material was determined according to GB / T 1033.1-2008, and the wear amount was calculated according to V = (m0-m1) × 1000 / ρ, where V is the wear amount in mm. 3 m0 and m1 are the sample masses before and after the test, respectively, in grams; ρ is the sample density, in g / cm³. 3 The average friction coefficient is the arithmetic mean of the friction coefficients collected during the 2-hour test.
[0066] Friction stability test: Based on the friction coefficient collected within 30-120 minutes after the start of the sliding friction and wear test, the standard deviation of the friction coefficient is calculated and used as the friction coefficient fluctuation value.
[0067] Test of whitening degree of surface after grinding: The L value of the friction surface of the sample before and after the friction test was measured using a spectrophotometer. Three positions were selected in the middle of the grinding mark for each sample for measurement, according to ΔL=L 磨后 -L 磨前 Calculate the change in brightness after grinding.
[0068] The area ratio of wear marks and pits was tested by scanning electron microscope at equal magnification and at equal intervals. Five fields of view of the middle part of the wear mark were collected. The percentage of the pit projection area to the total area of the field of view was calculated by image analysis software. The average value of the five fields of view was taken as the area ratio of wear marks and pits.
[0069] The test results are shown in Table 1.
[0070] Table 1: Performance test results of black talc-modified low-carbon black abrasion-resistant polypropylene materials in Examples 1-4 and Comparative Examples 1-4
[0071]
[0072] From the test results of Example 1 and Comparative Example 1 in Table 1, it can be seen that without KH550 treatment of black talc powder, the surface of black talc lacks amino sites that can react with the residual anhydride groups in the partially zinc-neutralized maleic PP wax. The partially zinc-neutralized maleic PP wax mainly adheres to the surface of black talc through wetting and physical adsorption. Under repeated friction and shearing, the interface debonding and particle pull-out increase, resulting in an increase in wear. The detached particles participate in plowing and intermittently enter the friction interface, which increases the average friction coefficient and the friction coefficient fluctuation value. The pits and wear debris formed by particle pull-out increase surface light scattering, which increases the change value of brightness after grinding, and at the same time, the area ratio of wear pits increases.
[0073] As shown in Table 1, the test results of Example 1 and Comparative Example 2 indicate that without the addition of ZnO, the maleic PP wax cannot form a zinc carboxylate ion-associated structure. The interfacial layer mainly relies on the possible reaction connection between residual anhydride groups and amino-enriched black talc, as well as the wetting effect of the PP wax. Under continuous frictional shearing, the slippage and local detachment of interfacial layer chains increase, the load-bearing state of black talc particles and the lamellar peeling process are not stable enough, resulting in increased wear. Interfacial wear debris and particle pull-out increase frictional resistance, causing the average friction coefficient to increase and the friction coefficient fluctuation value to increase. The increase in wear pits and loose wear debris increases the change in brightness after grinding and the area ratio of wear pits.
[0074] As shown in Table 1, the test results of Example 1 and Comparative Example 3 reveal that, omitting the pre-anchoring hot mixing of amino-enriched black talc and partially zinc-neutralized maleic PP wax, both directly enter the polypropylene melt. Due to melt dilution and extrusion residence time limitations, the partially zinc-neutralized maleic PP wax tends to disperse in the copolymerized PP, resulting in decreased contact and adhesion with the black talc surface. During friction, black talc particles are more prone to interfacial debonding and overall pull-out, leading to increased wear. The discontinuous generation and discharge of detached particles at the friction interface increases the average friction coefficient and its fluctuation. The surface pits and rough areas formed by particle detachment increase light scattering, leading to a greater change in post-grind brightness and an increase in the area ratio of wear pits.
[0075] As shown in Table 1, the test results of Example 1 and Comparative Example 4 indicate that after the pre-anchored functional black talc is added through the main feed port, its melting residence time and shearing process increase. The pre-formed wax phase coating and interface connection may be subjected to continuous shearing action, and some black talc layers may also break or re-aggregate, resulting in a decrease in the retention of the pre-anchored interface in the final material. During the friction process, the increase in particle pull-out and wear debris formation leads to an increase in wear amount and average friction coefficient; the migration of wear debris within the friction interface causes changes in frictional resistance, increasing the fluctuation value of the friction coefficient; the increase in pits and discontinuous wear debris coverage area within the wear track increases the change in brightness after grinding and the area ratio of wear track pits.
[0076] The above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.
Claims
1. A method for preparing a talc-modified low-carbon-black wear-resistant polypropylene material, characterized in that, Includes the following steps: S1: KH550 pre-hydrolyzed liquid is atomized and sprayed into continuously agitated black talc powder, and then subjected to heating and aging treatments in sequence to obtain amino-enriched black talc. S2: Mix ZnO with PP wax to obtain wax-loaded ZnO predispersant; add maleic anhydride-grafted PP wax and fatty alcohol to a co-rotating twin-screw extruder for reaction, then add the wax-loaded ZnO predispersant to continue the reaction to obtain partially zinc-neutralized maleic PP wax; S3: The amino-enriched black talc is hot-mixed with the partially zinc-neutralized maleic PP wax to obtain pre-anchored functional black talc. S4: Add copolymer PP and PP carrier carbon black masterbatch to a co-rotating twin-screw extruder. After the copolymer PP melts, add the pre-anchored functional black talc through the side feed port. After melt blending, obtain a black talc-modified low carbon black wear-resistant polypropylene material.
2. The preparation method according to claim 1, characterized in that, In step S1, the D50 of the black talc powder is 3-7 μm; the black talc powder is dried at 100-120℃ for 2-4 h; KH550 is added to a mixed solvent to prepare a silane solution with a KH550 mass concentration of 5-10 wt.%, wherein the mixed solvent is composed of ethanol and water, wherein the volume fraction of ethanol is 80-90 vol.%, and the remainder is water; the pH of the silane solution is adjusted to 4.5-5.5 with acetic acid; and the solution is allowed to stand at 15-25℃ for 30-60 min to hydrolyze, thereby obtaining the KH550 pre-hydrolyzed solution.
3. The preparation method according to claim 2, characterized in that, In step S1, the dried black talc powder is added to a high-speed mixer and continuously agitated and sprayed into the KH550 pre-hydrolyzed solution at 60-70℃ and 600-1200rpm. The mass ratio of the black talc powder to KH550 is 100:(0.4-0.6), and the spraying time is 10-30min. After spraying, the temperature is raised to 80-95℃ and mixing is continued for 10-30min. Then, it is matured at 105-115℃ for 20-40min. After cooling, it is sieved to obtain the amino-enriched black talc.
4. The preparation method according to claim 1, characterized in that, In step S2, the primary particle size of the ZnO is 20-100 nm, and the mass ratio of ZnO to PP wax is (18-22):(82-78). The ZnO and PP wax are added to a closed hot mixer and mixed at 300-800 rpm for 10-30 min at a temperature 10-20°C higher than the softening point of the PP wax and not higher than 150°C. The mixture is then cooled and crushed to obtain the wax-loaded ZnO pre-dispersion.
5. The preparation method according to claim 4, characterized in that, In step S2, the molar ratio of the grafted anhydride group to the fatty alcohol in the maleic anhydride-grafted PP wax is 1:(0.40-0.55). The maleic anhydride-grafted PP wax and the fatty alcohol are added to the co-rotating twin-screw extruder through the main feed port and reacted at 145-165℃ for 1-3 minutes. The fatty alcohol is hexadecyl alcohol or octadecyl alcohol.
6. The preparation method according to claim 5, characterized in that, In step S2, the mass ratio of the maleic anhydride-grafted PP wax to the wax-supported ZnO predispersant is 100:(1.0-1.4). After adding the wax-supported ZnO predispersant, the reaction is carried out at 150-165℃ for 1.5-3 min. During the reaction, the screw speed is 150-350 rpm, the total residence time of the material is 3-5 min, and the latter part is vacuum degassing under an absolute pressure of 10-40 kPa. After extrusion granulation, the partially zinc-neutralized maleic PP wax is obtained.
7. The preparation method according to claim 1, characterized in that, In step S3, the amino-enriched black talc is heated to 125-155℃, and then the partially zinc-neutralized maleic PP wax is added. The mass ratio of the amino-enriched black talc to the partially zinc-neutralized maleic PP wax is 100:(7-9). The mixture is hot-mixed at 300-800 rpm for 8-20 minutes. After the hot mixing is completed, the mixture is cooled, crushed, and sieved to obtain the pre-anchored functional black talc.
8. The preparation method according to claim 1, characterized in that, In step S4, the carbon black content in the PP carrier carbon black masterbatch is 35-45 wt.%.
9. The preparation method according to claim 8, characterized in that, In step S4, the melt blending temperature is 180-210℃, the screw speed is 200-400rpm, and the melt blending time is 1-3min; in the subsequent stage, vacuum degassing is performed under an absolute pressure of 10-40kPa, and the material is obtained by extrusion granulation to obtain the black talc-modified low carbon black wear-resistant polypropylene material.
10. A talc-modified, low-carbon-black, wear-resistant polypropylene material, characterized in that, The material comprises copolymer PP, carbon black, and pre-anchored functional black talc; based on 100 wt.% of the total mass of the low-carbon-black abrasion-resistant polypropylene material modified with the black talc, the carbon black content is 0.25-0.50 wt.%; the pre-anchored functional black talc comprises amino-enriched black talc and partially zinc-neutralized maleic PP wax, the amino-enriched black talc comprising black talc powder and a hydrolysis condensate of KH550, and the partially zinc-neutralized maleic PP wax formed by a melt reaction of maleic anhydride-grafted PP wax, fatty alcohol, ZnO, and PP wax.
11. The talc-modified low-carbon-black abrasion-resistant polypropylene material according to claim 10, characterized in that, Based on a total mass of 100 wt.% of the black talc-modified low carbon black wear-resistant polypropylene material, the content of the pre-anchoring functional black talc is 15-24 wt.%.
